Implementing the IBM system storage SAN volume controller with IBM Spectrum Virtualize V8.2.1 - Tate, Jon (IBM Corporation, International Technical Support Organization, 2019)
This IBM® Redbooks® publication is a detailed technical guide to the IBM System Storage® SAN Volume Controller (SVC), which is powered by IBM Spectrum™ Virtualize V8.2.1. IBM SAN Volume Controller is a virtualization appliance solution that maps virtualized volumes that are visible to hosts and applications to physical volumes on storage devices. Each server within the storage area network (SAN) has its own set of virtual storage addresses that are mapped to physical addresses. If the physical addresses change, the server continues running by using the same virtual addresses that it had before. Therefore, volumes or storage can be added or moved while the server is still running. The IBM virtualization technology improves the management of information at the block level in a network, which enables applications and servers to share storage devices on a network.
Number on back cover: SG24-7933-07. - "This edition applies to IBM Spectrum Virtualize V8.2.1 and the associated hardware and software detailed within. Note that the screen captures included within this book might differ from the generally available (GA) version, because parts of this book were written with pre-GA code"--Page 2 of cover. - Includes bibliographical references. - Online resource; title from cover (Safari, viewed September 27, 2019)
Keywords: Storage area networks (Computer networks); Virtual storage (Computer science); IBM computers; Réseaux de stockage (Informatique); Ordinateurs; Mémoires virtuelles; IBM (Ordinateurs)